An investigation of loneliness and related factors among the spouses of personnel deployed to long-term naval missions - M Amidi Mazaheri; Sh Mirzaman; Z Manouchehri; Z Torabi (فصلنامه ابن سینا)
Background: Given the important effects of loneliness on health and it has not been studied precisely in our country among the spouses of personnel deployed to long-term missions, therefore, the current study was done to investigate loneliness and related factors among spouses of naval personnel.